Synthesis of zinc oxide modified magnetic nano-chitosan - Zananaro, Leonardo Vidal; Vincensi, Enzo Cassol; Silveira da Silva, Adrine; Rhoden, Daniele Soares Basso; Montagner, Taise Schuster; Zanella, Ivana; Rhoden, Cristiano Rodrigo Bohn (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
The global population experienced an unprecedented viral infection known as SARS-CoV-2. Due to it being a novel virus, the range of effective medications was limited. Nevertheless, the occurrence of undesired and often potentially toxic effects further restricted the choices of medications. Considering this, nanotechnology, through manipulating matter, allows many compounds to exhibit nanoscale properties, reducing toxicity, increasing selectivity, and lowering the required dosage. Considering the excellent properties of the nanoparticles mentioned in this study, the objective was to synthesize magnetic nanoparticles doped with zinc oxide, aiming at developing a nanomaterial with antiviral activity. Once the nanoparticles are obtained, subsequent biological assays will be conducted to evaluate their activity against the SARS-CoV-2 virus.